The effect of self-awareness in the attitude and performance on speaking skills of eight-grade students of a school in Chunchi – Chimborazo - Ordoñez Silva, Liliana Jaqueline (2021)
This study explores the effects of applying self-awareness activities and strategies in the attitudes and performance on speaking skills in eighth-grade students from a rural school. This study seeks to support students in improving their communicative skills due to the difficulty they represent for most learners. The research was performed with two groups of students, one class A, and one class B. Participants from Class A received Social Emotional Learning instruction using explicit self-awareness skills through content and activities. The instruments used were surveys and speaking rubrics. The data analysis showed that even though self-awareness does not directly influence the learners´ performance in speaking, it improves their attitudes towards learning and contributes to their self-perception. These factors could benefit them in a long-term period.